2015
DOI: 10.1002/jnr.23578
|View full text |Cite
|
Sign up to set email alerts
|

Brain changes associated with thromboxane receptor antagonist SQ 29,548 treatment in a mouse model

Abstract: The purpose of this study was to characterize behavioral and physiological effects of a selective thromboxane receptor (TP) antagonist, SQ 29,548, in the C57BL/6 mouse model. At six months of age, male mice were given either sham or drug intraperitoneal injections for three days at a dose of 2mg/kg each day. On the day after the final injection mice were subjected to behavioral testing paradigms before brain collection. Left hemisphere hippocampi were collected from all mice for protein analysis via western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…TXA2R, which is mainly distributed in platelets, has been suggested to be an important membrane receptor in the coagulation and inflammation processes in humans (6). In recent years, it has been reported that TXA2R also exists in nerve cells (5), and participates in the regulation of a series of physiological processes in peripheral and central nervous cells (5,24,25). Our previous study observed that the mutation of TXA2R affected the coagulation system function and further affected the onset of cI (6).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…TXA2R, which is mainly distributed in platelets, has been suggested to be an important membrane receptor in the coagulation and inflammation processes in humans (6). In recent years, it has been reported that TXA2R also exists in nerve cells (5), and participates in the regulation of a series of physiological processes in peripheral and central nervous cells (5,24,25). Our previous study observed that the mutation of TXA2R affected the coagulation system function and further affected the onset of cI (6).…”
Section: Discussionmentioning
confidence: 95%
“…SH-SY5Y, a neuron cell line, is widely used in studies investigating neurological disorders (27,28) and oxidative stress in nerve cells (17,28). SQ29548 has been proposed to be a specific, reliable and safe TXA2R antagonist (29), and is broadly utilized in studies on TXA2R (7,25,30,31). H 2 O 2 , as one of main ROS products in cellular oxidative stress (32), is typically used to establish an in vitro oxidative stress cell model (23,33).…”
Section: Discussionmentioning
confidence: 99%
“…However, this mechanism is rather convoluted and implicates COX as a source and regulator of a number of vasodilators and vasoconstrictors and their receptors. As part of arachidonic acid cascade, COX activity is required for producing CBF vasoactive PGs such as PGE 2 , PGF 2α , TXA 2 , prostacyclins, and their receptors (Davidge, 2001; Li et al., 1997; Rebel et al., 2015). In addition, COX catabolizes P450 products that also regulate CBF, such as vasodilator epoxyeicosatrienoic acids, and vasoconstrictor 20‐hydroxyeicosatetraenoic acid to produce vasoconstrictor endoperoxides or vasodilator prostanoids (Alkayed et al., 1996; Iliff et al., 2009, 2010; Imig, 2016; Toth et al., 2011; Zhang et al., 2008).…”
Section: Discussionmentioning
confidence: 99%